We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+1
1
460
1
avatar

Yx+XX+Xy= ab

  Find dy/dx...?

 Jul 25, 2017
 #1
avatar+22188 
+1

Find dy/dx

Yx+XX+Xy= ab

 

\(\begin{array}{|rcll|} \hline y^x+x^x+x^y &=& a^b \\ y^x+x^x+x^y -a^b &=& 0 \\ \hline \end{array} \)

 

Formula:

\(\begin{array}{|rcll|} \hline \frac{dy}{dx} = - \dfrac{F_x}{F_y} \\ \hline \end{array} \)

 

\(\mathbf{F_x =\ ?} \begin{array}{|rcll|} \hline F_x &=& \frac{d }{dx}y^x + \frac{d }{dx}x^x + \frac{d }{dx}x^y + \frac{d }{dx}a^b \\\\ h &=& y^x \quad & | \quad \ln() \\ \ln(h) &=& x\cdot \ln(y) \\ \frac{h'}{h} &=& \ln(y) \\ h' &=& h\cdot \ln(y) \\ h' &=& y^x\cdot \ln(y) \\ \mathbf{ \frac{d }{dx}y^x } & \mathbf{=} & \mathbf{ y^x\cdot \ln(y) } \\\\ h &=& x^x \quad & | \quad \ln() \\ \ln(h) &=& x\cdot \ln(x) \\ \frac{h'}{h} &=& x\cdot \frac{1}{x} + 1\cdot \ln(x) \\ h' &=& h \cdot \Big( 1+\ln(x) \Big) \\ \mathbf{ \frac{d }{dx}x^x } & \mathbf{=} & \mathbf{ x^x \cdot \Big( 1+ \ln(x) \Big) } \\\\ h &=& x^y \quad & | \quad \ln() \\ \ln(h) &=& y\cdot \ln(x) \\ \frac{h'}{h} &=& \frac{y}{x} \\ h' &=& h \cdot \frac{y}{x} \\ h' &=& x^y \cdot \frac{y}{x} \\ \mathbf{ \frac{d }{dx}x^y } & \mathbf{=} & \mathbf{ x^y \cdot \frac{y}{x} } \\\\ \mathbf{ \frac{d }{dx}a^b } & \mathbf{=} & \mathbf{ 0 } \\ \hline \end{array} \)

 

\(\mathbf{F_y =\ ?} \begin{array}{|rcll|} \hline F_y &=& \frac{d }{dy}y^x + \frac{d }{dy}x^x + \frac{d }{dy}x^y +\frac{d }{dy}a^b \\\\ h &=& y^x \quad & | \quad \ln() \\ \ln(h) &=& x\cdot \ln(y) \\ \frac{h'}{h} &=& \frac{x}{y} \\ h' &=& h\cdot \frac{x}{y} \\ h' &=& y^x\cdot \frac{x}{y} \\ \mathbf{ \frac{d }{dy}y^x } & \mathbf{=} & \mathbf{ y^x\cdot \frac{x}{y} } \\\\ \mathbf{ \frac{d }{dy}x^x } & \mathbf{=} & \mathbf{ 0 } \\ h &=& x^y \quad & | \quad \ln() \\ \ln(h) &=& y\cdot \ln(x) \\ \frac{h'}{h} &=& \ln(x) \\ h' &=& h \cdot \ln(x) \\ h' &=& x^y \cdot \ln(x) \\ \mathbf{ \frac{d }{dy}x^y } & \mathbf{=} & \mathbf{ x^y \cdot \ln(x) } \\\\ \mathbf{ \frac{d }{dy}a^b } & \mathbf{=} & \mathbf{ 0 } \\ \hline \end{array}\)

 

\(\begin{array}{|rcll|} \hline \frac{dy}{dx} &=& - \dfrac{F_x}{F_y} \\\\ \frac{dy}{dx} &=& - \dfrac{ y^x\cdot \ln(y) + x^x \cdot \Big( 1+ \ln(x) \Big) + x^y \cdot \frac{y}{x} + 0 } { y^x\cdot \frac{x}{y} + 0 + x^y \cdot \ln(x) + 0 } \\\\ \frac{dy}{dx} &=& - \dfrac{ y^x\cdot \ln(y) + x^x \cdot \Big( 1+ \ln(x) \Big) + x^y \cdot \frac{y}{x} } { y^x\cdot \frac{x}{y} + x^y \cdot \ln(x) } \\\\ \frac{dy}{dx} &=& - \dfrac{ y^x\cdot \ln(y) + x^x \cdot \Big( 1+ \ln(x) \Big) + x^{y-1} \cdot y } { y^{x-1}\cdot x + x^y \cdot \ln(x) } \\\\ \mathbf{ \frac{dy}{dx} } & \mathbf{=} & \mathbf{ - \dfrac{ y^x\cdot \ln(y) + x^x \cdot \Big( 1+ \ln(x) \Big) + x^{y-1} \cdot y } { x^y \cdot \ln(x) + y^{x-1}\cdot x } } \\ \hline \end{array}\)

 

laugh

 Jul 25, 2017

7 Online Users

avatar
avatar
avatar